Early Tree Diversity and Composition Effects on Topsoil Chemistry in Young Forest Plantations Depend on Site Context - Dhiedt, Els; Verheyen, Kris; De Smedt, Pallieter; Ponette, Quentin; Baeten, Lander (Ecosystems (New York), 2021)
Trees have a strong influence on the chemical properties of the soil in which they grow. Establishing plantations with different tree species combinations thus potentially leads to divergence in soil chemistry. To study the degree to which differentiation already occurs during the first years after establishment, we made use of a biodiversity–ecosystem functioning experiment in Belgium, FORBIO. The multi-site experiment replicates tree species richness (1–4 species) and composition in three sites. The sites represent contrasting site contexts, mostly land-use history, soil, and climate. Soil samples (0–10 cm) were taken at the time of planting and approximately 8 years later. We measured the total C and N concentration, the Olsen P, the pH-H₂O, and the concentration of base and Al cations. The change in chemical composition was strongly dependent on site conditions including former land use. Afforestation on former cropland had a positive impact on total C and Olsen P and a negative effect on base cations and pH. On sites reforested after clearcut, soil texture and particular site preparation played an important role. On top of that, we found several significant effects of species composition. Strongest composition effects were detected in the reforested site on loamy soil with little soil disturbance. This study highlights that species choice can already affect soil chemistry in early stages of forest development, but that the nature of the effects may strongly depend on the context in which the plantations are established. Further research is needed to identify the most important contextual factors.